Pressure-sensitive adhesive matrix with high plasticity resistance as well as preparation method and application of pressure-sensitive adhesive matrix
By developing a high-plastic resistance hydroxyl-containing polyacrylate pressure-sensitive glue matrix, the cold flow problem caused by poor plastic resistance in the prior art was solved, and the effects of high drug loading and efficient delivery were achieved, meeting the FDA's review standards.
Patent Information
- Application Number
- CN202411044192.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing acrylate pressure-sensitive adhesives have poor plasticity after loading drugs, resulting in cold flow problems, affecting the therapeutic effect and storage difficulty of the patch, and are difficult to pass the FDA review.
A high-plastic resistance hydroxyl-containing polyacrylate pressure-sensitive glue matrix is used, which consists of acrylate soft monomer, hard monomer, functional monomer and silicone monomer. By controlling the molecular weight and crosslinking degree of the polymer, its glass transition temperature and adhesion are adjusted.
It achieves high plastic resistance, high drug loading capacity and high drug delivery ability, avoids cold flow problems, improves the stability and therapeutic effect of the patch, and meets the FDA's review standards.
Smart Images

Figure CN119591776A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a transdermal drug delivery patch matrix, in particular to a high-plasticity-resistant pressure-sensitive adhesive matrix and a preparation method and application thereof. Background Art
[0002] Transdermal drug delivery patches have the advantages of avoiding the first-pass liver effect of drugs, gastrointestinal irritation and improving bioavailability, which can improve patient compliance.
[0003] At present, in the percutaneous administration patch matrix, the listed pressure-sensitive adhesive products of countries such as the U.S. and Germany are mainly used. The commodity pressure-sensitive adhesive types listed mainly contain acrylates, polyisobutylenes and silicone pressure-sensitive adhesives, wherein the acrylate pressure-sensitive adhesives occupy more than half of the market share because of the good miscibility with the vast majority of drugs. However, the plastic resistance of the acrylate pressure-sensitive adhesive products listed abroad is poor, and there are many reports of cold flow problems. Cold flow can cause the reduction of patch therapeutic effect and the increase of storage difficulty, and makes the patch products in the planned application difficult to pass the review of the U.S. Food and Drug Administration (FDA).
[0004] Among acrylic pressure-sensitive adhesives, there are non-functional group type, carboxyl group type and hydroxyl group type. Hydroxyl-containing polyacrylate pressure-sensitive adhesives are widely used in transdermal drug delivery systems due to their universal applicability to acidic and alkaline drugs. However, the addition of drug molecules increases the relaxation of polymer chains, and at the same time, drug molecules destroy the interaction between groups in the pressure-sensitive adhesive. The addition of drug molecules breaks the balance between the adhesion and cohesion of the pressure-sensitive adhesive in the above way. Traditionally, the balance between adhesion and cohesion of pressure-sensitive adhesives is adjusted by controlling the molecular weight, polydispersity, branching and cross-linking of the polymer, but these methods of increasing cohesion usually reduce adhesion or reduce drug delivery performance. Summary of the invention
[0005] Based on the deficiencies of the prior art, the purpose of the present invention is to provide a hydroxyl polyacrylate pressure-sensitive adhesive matrix with high plastic resistance to solve the cold flow problem after loading drugs. The pressure-sensitive adhesive matrix not only has high plastic resistance, but also has high drug loading capacity and high drug delivery capacity.
[0006] The highly plastic-resistant pressure-sensitive adhesive matrix according to a specific embodiment of the present invention is made of the following raw materials in parts by weight:
[0007] 60-90 parts of acrylate soft monomer, 5-35 parts of acrylate hard monomer, 10-35 parts of acrylate functional monomer, and 0.001-5 parts of silicone monomer.
[0008] The pressure-sensitive adhesive matrix obtained in the present invention is a random copolymer, wherein the organosilicon monomer can cross-link the copolymer to improve its anti-plastic effect, and at the same time, the glass transition temperature of the copolymer can be reduced by using the acrylate soft monomer, and the acrylate hard monomer can increase the glass transition temperature of the copolymer. The glass transition temperature of the copolymer can be precisely adjusted by matching the acrylate soft monomer and the acrylate hard monomer in a specific ratio. The acrylate functional monomer is used to adjust the drug loading and release capacity of the copolymer.
[0009] According to the highly plastic resistant pressure-sensitive adhesive matrix of the specific embodiment of the present invention, the acrylic ester soft monomer includes one or more combinations of isooctyl acrylate, n-butyl acrylate, and ethyl acrylate.
[0010] According to the highly plastic resistant pressure sensitive adhesive matrix of the specific embodiment of the present invention, the acrylic acid ester hard monomer comprises one or more combinations of methyl acrylate, methyl methacrylate and vinyl acetate.
[0011] According to the highly plastic resistant pressure-sensitive adhesive matrix of the specific embodiment of the present invention, the acrylate functional monomer includes one or more combinations of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, acrylamide, and acrylic acid.
[0012] According to the highly plastic resistant pressure sensitive adhesive matrix of the specific embodiment of the present invention, the silicone monomer includes one or more combinations of methylvinyldimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and 3-(N-allylamino)propyltrimethoxysilane.
[0013] According to a specific embodiment of the present invention, a method for preparing a highly plastic-resistant pressure-sensitive adhesive matrix comprises the following steps:
[0014] (1) Put the raw materials into a reaction kettle, add the solvent, and mix them evenly;
[0015] (2) Control the temperature of the reactor at 70-80°C and add initiator;
[0016] (3) After maintaining the reaction process for 10-12 hours, the mixture is cooled to room temperature to obtain the pressure-sensitive adhesive matrix.
[0017] According to the method for preparing a highly plastic resistant pressure-sensitive adhesive matrix in a specific embodiment of the present invention, in step (1), the solvent is selected from one or more combinations of ethyl acetate, chloroform, acetone, and ethanol.
[0018] According to the method for preparing a highly plastic-resistant pressure-sensitive adhesive matrix in a specific embodiment of the present invention, the initiator is selected from one or more combinations of benzoyl peroxide, 2,2-azobisisobutyronitrile, azoisobutylcyanamide, isopropylbenzene hydroperoxide, and potassium persulfate.
[0019] The present invention also provides application of the pressure-sensitive adhesive matrix in a transdermal administration preparation.
[0020] The present invention also provides a transdermal patch, which comprises the above-mentioned pressure-sensitive adhesive matrix and active ingredients dispersed in the pressure-sensitive adhesive matrix.
[0021] Preferably, the active ingredient is an acidic or alkaline drug.
[0022] More preferably, the active ingredients involve drugs including but not limited to ketoprofen, diclofenac, ibuprofen, tulobuterol, oxybutynin, levamlodipine, mirtazapine, palonosetron, lidocaine, prilocaine, and isosorbide dinitrate.
[0023] The present invention also provides a method for preparing a transdermal absorption patch, comprising: dissolving an active ingredient (sufficient drug) in an organic solvent and then dispersing the mixture in a pressure-sensitive adhesive, stirring the mixture evenly and then transferring and coating the mixture on a release layer, drying the mixture at 40-75° C. for 10-60 min, then covering the mixture with a backing layer, and punching the mixture into transdermal absorption patches of a certain size and specification.
[0024] The thickness of the drug-loaded pressure-sensitive adhesive of the present invention can be 50-140 μm.
[0025] The material of the backing layer of the transdermal absorption patch is one of a polyester film or paper treated with silicone oil for anti-adhesion or containing fluorine, and a polyester film coated with fluorine polymer.
[0026] The dosage of the drugs in the transdermal absorption patch of the present invention can be selected as follows: 5-20wt% ketoprofen, 1-10wt% diclofenac, 10-25wt% ibuprofen, 10-20wt% tulobuterol, 10-25wt% oxybutynin, 1-20wt% levamlodipine, 5-15wt% mirtazapine, 5-15wt% palonosetron, 10-30wt% lidocaine, 10-30wt% prilocaine, and 10-30wt% isosorbide dinitrate.
[0027] The structural formula of some polyacrylate pressure-sensitive adhesives is as follows:
[0028]
[0029] The raw materials and the proportions used are: 10-50 parts of methyl acrylate, 40-90 parts of isooctyl acrylate, 10-35 parts of hydroxyethyl acrylate and 0.01-2 parts of 3-(isobutyleneoxy)propyltrimethoxysilane, wherein the value range of x is between 1 and 10000, the value range of y is between 1 and 8000, the value range of m is between 1 and 2000, and the value range of n is between 1 and 1000.
[0030]
[0031] The raw materials and the proportions used are: 10-50 parts of methyl acrylate, 40-90 parts of isooctyl acrylate, 10-35 parts of hydroxyethyl acrylate and 0.01-2 parts of 3-(N-allylamino)propyltrimethoxysilane, wherein the value range of x is between 1 and 10000, the value range of y is between 1 and 8000, the value range of m is between 1 and 2000, and the value range of n is between 1 and 1000.
[0032]
[0033] The raw materials and the proportions used are: 10-50 parts of methyl acrylate, 40-90 parts of n-butyl acrylate, 10-35 parts of hydroxyethyl acrylate and 0.01-2 parts of 3-(N-allylamino)propyltrimethoxysilane, wherein the value range of x is between 1 and 10000, the value range of y is between 1 and 8000, the value range of m is between 1 and 2000, and the value range of n is between 1 and 1000.
[0034] The present invention introduces monomers containing siloxane groups, and through the covalent bonds formed between the siloxane groups, a large number of cross-linked networks are formed inside the polymer chain, thereby exerting an anti-plastic effect.
[0035] Beneficial effects of the present invention:
[0036] The pressure-sensitive adhesive matrix of the present invention is a random copolymer, and its weight average molecular weight (M n ) is between 300000Da and 700000Da, the polydispersity coefficient is between 1.1 and 1.5, the solid content is between 40 and 60%, and the glass transition temperature is -70°C to -15°C.
[0037] The pressure-sensitive adhesive of the present invention has high anti-plasticity, and after loading drugs, the cohesive force is significantly improved, while the adhesion is maintained at a high level, showing an excellent anti-plastic effect; in addition, the pressure-sensitive adhesive of the present invention also has good drug loading capacity and efficient drug delivery capability. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 It shows the cold flow test results of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive.
[0040] Figure 2 The in vitro skin permeation curves of the drugs in Examples 20, 24 and 28 are shown.
[0041] Figure 3 The in vitro skin permeation curves of the drugs in Examples 21, 25 and 29 are shown.
[0042] Figure 4 The in vitro skin permeation curves of the drugs in Examples 22, 26 and 30 are shown.
[0043] Figure 5 The in vitro skin permeation curves of the drugs in Examples 23, 27 and 31 are shown.
[0044] Figure 6 The in vivo pharmacokinetic test results in Examples 20, 24 and 28 are shown.
[0045] Figure 7 The in vivo pharmacokinetic test results in Examples 23, 27 and 31 are shown. DETAILED DESCRIPTION
[0046] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0047] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0048] The weight parts mentioned in the present invention may be kilograms, kilograms or grams.
[0049] In the present invention, the backing layer used is not particularly limited as long as it can be used for a patch, and preferably a polyethylene composite film, an ethylene / vinyl acetate copolymer film, a polyurethane film, a polyester composite film or a nonwoven fabric is used.
[0050] The anti-adhesive layer used is not particularly limited, and any anti-adhesive layer commonly used in patches can be used. Preferably, the surface is treated with silicone oil to release adhesion or is a fluorine-containing polyester film or a fluorine polymer coated polyester film.
[0051] In the present invention, high plastic resistance refers to the ability of the pressure-sensitive adhesive to effectively resist the plasticizing effect of plasticizers.
[0052] High drug loading capacity means that the pressure-sensitive adhesive has a higher drug loading capacity.
[0053] High drug delivery capability means that the pressure-sensitive adhesive has good in vitro drug delivery capability without obvious drug residue.
[0054] The present invention provides a pressure-sensitive adhesive matrix with high plastic resistance, which is made of the following raw materials in parts by weight:
[0055] 5-35 parts of acrylate hard monomer, 60-90 parts of acrylate soft monomer, 10-35 parts of acrylate functional monomer, and 0.001-5 parts of silicone monomer.
[0056] Preferably, the weight proportion of the acrylate hard monomer can be selected from 10-35 parts, 15-35 parts, 20-35 parts, 25-35 parts, 26-35 parts, 27-35 parts, 27-32 parts, or the weight proportion of the acrylate hard monomer is selected from any value in the range of 5-35 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts.
[0057] Preferably, the weight proportion of the acrylate soft monomer can be selected from 65-90 parts, 65-85 parts, 65-80 parts, 65-75 parts, or the weight proportion of the acrylate soft monomer can be selected from any value between 60 and 90 parts, for example, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 88 parts, 89 parts, and 90 parts.
[0058] Preferably, the weight proportion of the acrylate functional monomer can be selected from 10-30 parts, 10-25 parts, 15-25 parts, 15-30 parts, or the weight proportion of the acrylate functional monomer can be selected from any value in the range of 10-35 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 22 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts.
[0059] Preferably, the weight proportion of the organosilicon monomer can be selected from 0.01-5 parts, 0.02-5 parts, 0.03-5 parts, 0.03-4 parts, 0.03-3 parts, 0.03-2 parts, 0.03-1 parts, 0.03-0.5 parts, 0.03-0.1 parts, or the weight proportion of the organosilicon monomer is selected from any value in 0.001-5 parts, for example, 0.001 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts.
[0060] The acrylic acid ester hard monomer of the present invention is selected from methyl acrylate, methyl methacrylate, and vinyl acetate;
[0061] The acrylic soft monomer is selected from isooctyl acrylate, n-butyl acrylate, and ethyl acrylate;
[0062] The functional monomer is selected from hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide and acrylic acid; preferably, the functional monomer is selected from hydroxyethyl methacrylate, hydroxyethyl acrylate and hydroxypropyl acrylate;
[0063] The organic silicon monomer is selected from methylvinyldimethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and 3-(N-allylamino)propyltrimethoxysilane.
[0064] The initiator of the present invention comprises one or more combinations of benzoyl peroxide, 2,2-azobisisobutyronitrile, azoisobutylcyanoformamide, cumene hydroperoxide and potassium persulfate.
[0065] The dilution solvent of the present invention comprises one or more combinations of ethyl peroxide, chloroform, acetone and ethanol.
[0066] Example 1 (control group without silicon)
[0067] Mix the monomers methyl acrylate, isooctyl acrylate and hydroxyethyl acrylate in a ratio of 30:70:25, add ethyl acetate in an amount equal to the weight of the monomers, control the temperature at 75°C, add 0.4% of the weight of the monomer as the initiator 2,2-azobisisobutylnitrile, and react for 24 hours to generate a hydroxyl-containing polyacrylate pressure-sensitive adhesive.
[0068] Example 2
[0069] The monomers vinyl acetate, isooctyl acrylate, hydroxyethyl methacrylate, and 3-methylvinyldimethoxysilane are mixed in a ratio of 30:70:20:0.05, and acetone in an amount equal to the weight of the monomers is added. The temperature is controlled at 75°C, and 0.4% of the weight of the monomer as an initiator 2,2-azobisisobutylnitrile is added. The reaction is carried out for 10 hours to generate a silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive.
[0070] Example 3
[0071] The monomers methyl acrylate, ethyl acrylate, hydroxyethyl methacrylate, and 3-(N-allylamino)propyltrimethoxysilane are mixed in a ratio of 30:70:25:0.05, and acetone in an amount equal to the weight of the monomers is added. The temperature is controlled at 75°C, and 0.4% of the weight of the monomer as an initiator 2,2-azobisisobutylnitrile is added. The reaction is carried out for 12 hours to generate a silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive.
[0072] Example 4
[0073] The monomers methyl acrylate, isooctyl acrylate, hydroxyethyl acrylate, and 3-(isobutyleneoxy)propyltrimethoxysilane are mixed in a ratio of 30:70:25:0.5, and ethyl acetate in an amount equal to the weight of the monomers is added. The temperature is controlled at 75°C, and 0.4% of the weight of the monomer as an initiator 2,2-azobisisobutylnitrile is added. The reaction is carried out for 12 hours to generate a silicone-modified hydroxy-containing polyacrylate pressure-sensitive adhesive.
[0074] Example 5
[0075] The monomers methyl methacrylate, butyl acrylate, hydroxypropyl acrylate, and 3-(N-allylamino)propyltrimethoxysilane are mixed in a ratio of 30:70:25:0.5, and ethyl acetate in an amount equal to the weight of the monomers is added. The temperature is controlled at 75°C, and 0.4% of the weight of the monomer as an initiator 2,2-azobisisobutylnitrile is added. The reaction is carried out for 12 hours to generate a silicone-modified hydroxy-containing polyacrylate pressure-sensitive adhesive.
[0076] Determination of maximum drug loading
[0077] Examples 6-9 use the pressure-sensitive adhesive matrix of Example 1
[0078] Example 6
[0079] Ketoprofen was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0080] Example 7
[0081] Diclofenac was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0082] Example 8
[0083] Tulobuterol was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0084] Example 9
[0085] Oxybutynin was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric and punched to prepare a patch with a thickness of 90 μm.
[0086] Examples 10-13 use the pressure-sensitive adhesive matrix of Example 4
[0087] Example 10
[0088] Ketoprofen was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0089] Embodiment 11
[0090] Diclofenac was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0091] Example 12
[0092] Tulobuterol was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0093] Example 13
[0094] Oxybutynin was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric and punched to prepare a patch with a thickness of 90 μm.
[0095] Examples 14-17 use commercially available 87-2287
[0096] Embodiment 14
[0097] Ketoprofen was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0098] Embodiment 15
[0099] Diclofenac was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0100] Example 16
[0101] Tulobuterol was dispersed in 2 g of hydroxylated polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0102] Embodiment 17
[0103] Oxybutynin was dispersed in 2 g of hydroxylated polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0104] Preparation of transdermal drug delivery patches
[0105] Embodiment 18
[0106] 2 g of hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 1) was evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0107] Embodiment 19
[0108] 2 g of the organosilicon-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) was evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric and punched to prepare a patch with a thickness of 90 μm.
[0109] Preparation of drug-containing transdermal patches
[0110] Embodiment 20
[0111] 0.15 g of ketoprofen was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0112] Embodiment 21
[0113] 0.05 g of diclofenac was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0114] Embodiment 22
[0115] 0.15 g of tulobuterol was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0116] Embodiment 23
[0117] 0.15 g of oxybutynin was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive (Example 1), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric and punched to prepare a patch with a thickness of 90 μm.
[0118] Embodiment 24
[0119] 0.15 g of ketoprofen was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0120] Embodiment 25
[0121] 0.05 g of diclofenac was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), uniformly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0122] Embodiment 26
[0123] 0.15 g of tulobuterol was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0124] Embodiment 27
[0125] 0.15 g of oxybutynin was dispersed in 2 g of silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4), evenly coated on the anti-adhesive layer, dried at 50° C. for 30 min, and then covered with a backing material including PVC or non-woven fabric and punched to prepare a patch with a thickness of 90 μm.
[0126] Embodiment 28
[0127] 0.15 g of ketoprofen was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0128] Embodiment 29
[0129] 0.05 g of diclofenac was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0130] Embodiment 30
[0131] 0.15 g of tulobuterol was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0132] Embodiment 31
[0133] 0.15 g of oxybutynin was dispersed in 2 g of hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287), evenly coated on the anti-adhesive layer, dried at 50°C for 30 min, and then covered with a backing material including PVC or non-woven fabric, and punched to prepare a patch with a thickness of 90 μm.
[0134] The present invention tests the pressure-sensitive adhesive matrix obtained in Examples 1-5, and the test items include relative molecular mass, solid content, glass transition temperature and polydispersity coefficient.
[0135] The present invention adopts gel permeation chromatography to measure the relative molecular mass of synthetic pressure-sensitive adhesive, and uses Waters Alliance e2695 equipped with a refractive index detector (Waters 2414) for analysis. Use Styragel HR5 single root chromatograph for measurement. Select tetrahydrofuran as eluent, flow rate is 1mL / min, the sample is dissolved in tetrahydrofuran for analysis (20μL, 20mg / mL), and the column temperature is set to 35°C. Mn and PDI values are determined according to the calibration curve. The standard curve is obtained using poly (methyl methacrylate) standard (Mn=208,700, 309,000, 389,000, 498,800 and 1,583,000Da).
[0136] The solid content determination method of the pressure-sensitive adhesive in the present invention is: the initial pressure-sensitive adhesive is weighed and placed in an oven for 24 hours to fully remove the organic solvent and obtain the dry adhesive weight. The ratio of the dry adhesive to the initial weight of the pressure-sensitive adhesive is the solid content of the pressure-sensitive adhesive.
[0137] The glass transition temperature of the pressure-sensitive adhesive of the present invention is determined by thermal analysis using a Mettler-Toledo thermal analyzer (DSC 1, Mettler-Toledo International, Zurich, Switzerland) to determine the glass transition temperature (Tg). Before measurement, the sample is added to the DSC crucible. The DSC crucible is placed at room temperature for 12 hours to evaporate the organic solvent. The sample is heated from -70°C to 10°C, the heating rate is 2°C / min, the modulation period is 35s, and the modulation temperature amplitude is ±1K. All measurements are repeated three times.
[0138] The test results are as follows:
[0139] Table 1. Solid content of different pressure-sensitive adhesives
[0140] Example 1 Example 2 Example 3 Example 4 Example 5 Solid content (%) 50.3 50.5 51.3 50.6 50.4
[0141] Table 2. Molecular weight and polydispersity coefficient of different pressure-sensitive adhesives
[0142] Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[M n (Yes)]]> 43500 44600 43680 44300 45730 Polydispersity coefficient 1.4 1.4 1.4 1.4 1.4
[0143] Table 3. Glass transition temperature of different pressure-sensitive adhesives
[0144] Example 1 Example 2 Example 3 Example 4 Example 5 Glass transition temperature(℃) -65.52 -63.28 -66.75 -67.82 -64.36
[0145] Application test 1: short-term crystallization experiment
[0146] A series of patches with different concentrations were prepared with a concentration gradient of 1%, and placed at room temperature for 1 month to observe the crystallization. The maximum concentration of the drug-containing patch without crystallization was the maximum drug loading capacity of the pressure-sensitive adhesive. The short-term crystallization test results of 17 are shown in Table 4.
[0147] Table 4. Maximum drug loading of different drugs in different pressure-sensitive adhesives
[0148] Example 6 Example 7 Example 8 Example 9 Drug loading (w / w, ±1%) 21 6 14 25 Example 10 Embodiment 11 Example 12 Example 13 Drug loading (w / w, ±1%) 21 6 14 25 Embodiment 14 Embodiment 15 Example 16 Embodiment 17 Drug loading (w / w, ±1%) 16 3 10 18
[0149] Conclusion: As shown in Table 4, the organosilicon-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) has a high drug loading capacity, which is significantly higher than that of the hydroxyl-containing polyacrylate pressure-sensitive adhesive ( 87-2287), and at the same time as the hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 1).
[0150] Application Test 2: Adhesion and Cold Flow
[0151] The adhesion and cold flow of the patches of Examples 18-27 were measured according to the adhesion test method of 0952 of the Chinese Pharmacopoeia (2020 edition).
[0152] (1) Initial adhesion test
[0153] The initial adhesion was measured by the rolling ball ramp stop method with a tilt angle of 30°.
[0154] (2) Adhesion test
[0155] The patch was adhered to a test steel plate, placed vertically, a 1 kg weight was hung along the direction of the patch, and the time from the patch sliding to falling off was recorded.
[0156] (3) Peel strength measurement
[0157] The 180° peel strength test method was used to measure the peel strength of the patch using a tensile testing machine.
[0158] Cold flow determination
[0159] The patch was punched into a circular patch with a diameter of 1.0 mm. Cold flow was induced for 12 h under the pressure of a 1 kg weight at room temperature (25 °C). The cold flow area was measured using ImajeJ (National Institutes of Health, USA), and the percentage of the cold flow area to the original patch area was calculated.
[0160] Table 5. Adhesion performance test results of different prescription patches
[0161]
[0162] Conclusion: If Figure 1 As shown in Table 5, compared with Example 18, the initial adhesion and peel strength of Examples 20-23 increased, and the sustained adhesion decreased significantly, indicating that the hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 1) was significantly plasticized after loading the drug, and the silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) after loading the drug, compared with Example 19, the sustained adhesion of Examples 24-27 increased by more than 10 times, while the initial adhesion and peel strength did not change significantly compared with before loading the drug, showing stronger anti-plastic performance; at the same time, the cold flow experiment showed that the silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) had excellent anti-cold flow ability.
[0163] Application test three: in vitro transdermal test
[0164] A horizontal Franz diffusion cell was used, with fresh rat abdominal skin as the transdermal barrier, the receptor medium was pH 7.4 (Examples 24, 25, 26, 28, 29, 30) / 5.8 (Examples 27, 31) phosphate buffer, a magnetic stirrer was continuously used during the experiment, the stirring speed was 400-600 rpm, the system temperature was 32°C, and the cumulative permeation of the patch for 24 hours was measured. The drug transdermal results are shown in Figure 2-5 The experimental results show that the pressure-sensitive adhesive prepared according to Example 1 and Example 4 is There was no significant difference in the in vitro transdermal results of 87-2287 loaded with four model drugs.
[0165] Conclusion: The silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) has efficient in vitro drug delivery performance.
[0166] Application Test 4
[0167] Using hydroxyl polyacrylate pressure-sensitive adhesive ( 87-2287, German Han high pressure sensitive adhesive company), hydroxyl polyacrylate pressure sensitive adhesive (Example 1) and silicone modified hydroxyl polyacrylate pressure sensitive adhesive (Example 4) were used for rat pharmacokinetic test. 15 rats were randomly divided into three groups, and the patch was given to the rats where the hair was removed from the abdomen. Blood was collected from the eye socket at a predetermined time point to measure the blood drug concentration. The patch was removed after 48 hours. The results are shown in Table 6 and Figure 6-7 .
[0168] Table 6. Pharmacokinetic parameters of 87-2287, Example 1 and Example 4 in rabbits after drug loading (n=5)
[0169]
[0170]
[0171] Conclusion: If Figure 6-7 As shown in Table 6, the silicone-modified hydroxyl-containing polyacrylate pressure-sensitive adhesive (Example 4) and the hydroxyl-containing polyacrylate pressure-sensitive adhesive ( There is no significant difference in the in vivo drug delivery behavior of the pressure-sensitive adhesive containing hydroxyl polyacrylate (Example 1), indicating that it exerts a high anti-plastic effect while still maintaining efficient in vivo drug delivery ability.
[0172] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A highly plastic resistant pressure-sensitive adhesive matrix, characterized in that: Made from the following raw materials in parts by weight: 60-90 parts of acrylate soft monomer, 5-35 parts of acrylate hard monomer, 10-35 parts of acrylate functional monomer, and 0.001-5 parts of silicone monomer.
2. The highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: The acrylic acid ester soft monomer includes one or more combinations of isooctyl acrylate, n-butyl acrylate, and ethyl acrylate.
3. The highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: The acrylic acid ester hard monomer includes one or more combinations of methyl acrylate, methyl methacrylate and vinyl acetate.
4. The highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: The acrylate functional monomer includes one or more combinations of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, acrylamide, and acrylic acid.
5. The highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: The organic silicon monomer includes one or more combinations of methylvinyldimethoxysilane, 3-(isomethacryloyloxy)propyltrimethoxysilane, and 3-(N-allylamino)propyltrimethoxysilane.
6. The method for preparing a highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Put the raw materials into a reaction kettle, add the solvent, and mix them evenly; (2) Control the temperature of the reactor at 70-80°C and add initiator; (3) After maintaining the reaction process for 10-12 hours, the mixture is cooled to room temperature to obtain the pressure-sensitive adhesive matrix.
7. The method for preparing a highly plastic-resistant pressure-sensitive adhesive matrix according to claim 6, characterized in that: In step (1), the solvent is selected from one or more combinations of ethyl acetate, chloroform, acetone and ethanol.
8. The highly plastic resistant pressure-sensitive adhesive matrix according to claim 1, characterized in that: In step (2), the initiator is selected from one or more combinations of benzoyl peroxide, 2,2-azobisisobutyronitrile, azoisobutylcyanamide, cumene hydroperoxide, and potassium persulfate.
9. Use of the pressure-sensitive adhesive matrix according to claims 1 to 5 or the pressure-sensitive adhesive matrix obtained by the preparation method according to any one of claims 5 to 8 in a transdermal drug delivery preparation.
10. A transdermal patch, characterized in that: The transdermal patch comprises the pressure-sensitive adhesive matrix described in claims 1-5 or the pressure-sensitive adhesive matrix obtained by the preparation method described in any one of claims 5-8, and an active ingredient dispersed in the pressure-sensitive adhesive matrix; preferably, the active ingredient is an acidic or alkaline drug.
Citation Information
Patent Citations
Transdermal therapeutic system containing nicotine and silicone acrylic hybrid polymer
CN111867570A
Transdermal patch
CN112891324A
Acrylate pressure-sensitive adhesive and application thereof
CN113004839A
Pressure-sensitive adhesive dispersing type red medicine patch and preparation method thereof
CN114748521A
Acrylate pressure-sensitive adhesive and preparation method thereof
CN118206941A